OTHR-20. Precision neuro-oncology in the real world. Opportunity and challenges from a UK Oncology Centre. (3rd June 2022) - Apps, John; Peet, Andrew; English, Martin; Adamski, Jenny
Abstract: The last five years has shown advances in the molecular classification of brain tumour, molecular profiling techniques and an increased use of targeted therapies. We reviewed the molecular analysis pathways and use of targeted agents at Birmingham Children's Hospital (BCH), a large ( 55 new cases/year) neuro-oncology centre, between 2016-2021. Having previously been analysed locally by limited directed immuno-histochemical stains and referral for specific genetic tests, tissue is now referred for a range of second histopathological opinions and in depth molecular classification, via methylation array, panel sequencing, RNA fusion analysis, and whole genome sequencing. These are accessed through different evolving pathways and consent processes, including referral to other centres, national reference laboratories, clinical studies, and local genetics laboratories with links to national sequencing infrastructures. Different routes result in different reporting structures, timescales and with varying levels of interpretation, often without adequate access to clinical information and context. 21 patients were treated on five targeted agent clinical trials (Afatanib (n=6), Biomede (n=3), eSmart(n=1), PARC (n=7), Vinilo (n=5)), with one patient on both Afatanib and PARC trials. A further two patients visited other centres for trials. Eight patients received MAPK pathway inhibitors through compassionate access pathways, with benefit, including radiological response, in four. Cardiac toxicity was observed in three and retinal oedema in one. Two patients received immune checkpoint inhibition, with rapid fatal enlargement, either progression or pseudo-progression, in one case. These rapid changes in diagnostic and management options offer new opportunities for patients, but bring challenges to the delivery of neuro-oncology services, including the logistics of sample, report, clinical trial, compassionate access management and the increased multi-specialist support required for monitoring and management of toxicities. Integration of targeted agents into the appropriate part of a patient's treatment strategy requires skilled interpretation of the benefits compared to conventional therapies.